(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Background: Although cancer (Ca) etiology can be multifactorial, it is nearly universally intertwined with genetic mutations that instigate tumor genesis or progression. This updated review aims at describing if this dispute remains meaningful based on a thorough literature survey. Methodology: This updated review was conducted over the last 2.5 decades using 3 (three) search engines: Web of Science (WoS), Pubmed and Science direct that encompassed all associated information and hypothetical considerations, globally, utilizing information from 1998 through 2022. All such, concepts, logically deducted explanations and scientifically assumed points if Ca remains hereditary is the main focus of this review. Results/ Findings: This appraisal on cancer, though yielded some instances of hereditariness in origin, mostly remains of genetic origin. Reportedly, cancers can be passed down from one family member to another through genes, and, may cause by genetic mutation present in eggs or sperms cell during fertilization which are actually considered as hereditary cancer, like breast, colon, and prostate cancer, as well as less common cancers, viz., pancreatic and ovarian cancer. Therefore, understanding the hereditary factors of Ca is critical not only for assessing the genetic contribution to cancer, but also for designing preventive and therapeutic strategies. It allows identifying people who are at a higher risk due to family history and/or genetic makeup, allow early detection through improved surveillance and, more importantly, for tailored therapeutic modality. By addressing recent advancement, this review will provide an overview on the hereditary factors of cancers and/or raising awareness on significant role of development in Ca genetics. The Journal of Ad-din Women’s Medical College; Vol. 11 (2), July 2023; p 48-57